An Adaptive Connectivity-based Centroid Algorithm for Node Positioning in Wireless Sensor Networks - Pratiarso, Aries; Kristalina, Prima (Politeknik Elektronika Negeri Surabaya (PENS), 2015)
In wireless sensor network applications, the position of nodes is randomly distributed following the contour of the observation area. A simple solution without any measurement tools is provided by range-free method. However, this method yields the coarse estimating position of the nodes. In this paper, we propose Adaptive Connectivity-based (ACC) algorithm. This algorithm is a combination of Centroid as range-free based algorithm, and hop-based connectivity algorithm. Nodes have a possibility to estimate their own position based on the connectivity level between them and their reference nodes. Each node divides its communication range into several regions where each of them has a certain weight depends on the received signal strength. The weighted value is used to obtain the estimated position of nodes. Simulation result shows that the proposed algorithm has up to 3 meter error of estimated position on 100x100 square meter observation area, and up to 3 hop counts for 80 meters communication range. The proposed algorithm performs an average error positioning up to 10 meters better than Weighted Centroid algorithm.Keywords: adaptive, connectivity, centroid, range-free.